BASIC PRINCIPLES OF DEVELOPMENT MECHANISMS OF CHILDREN AND ADOLESCENT TOURISM IN THE CITY OF TASHKENT (Marketing Journal, 2025)
The development of children and adolescent tourism is important not only for the tourism industry, but also for the educational and cultural -enlightenment development of society. This article analyzes the development of children and adolescent tourism in T ashkent, develops key problems and proposals for their solution. According to the results of the study, the infrastructure of childrenʼs tourism is not sufficiently developed, the efficiency of educational tourism is low, and economic factors are among the main problems hindering childrenʼs tourism. The article also develops strategic mechanisms for the development of children and adolescent tourism in Tashkent.
Keywords: childrenʼs tourism; adolescent tourism; tourism infrastructure; educational tourism; economic factors . 585